Dayah Cleric Views towards Aceh Community Plurality - Syarifuddin Abee; Hasan Bakti Nasution; Syahrizal Abas (Budapest International Research and Critics University, 2019)
Aceh Province is known as the Serambi area of Mecca which is supported by the strengthening of complete Islamic values. The socio-religious aspects such as the character of society and religious institutions in Aceh have made the Islamic spirit become a historical and cultural awareness for the people of Aceh. This is the case with the position of the Aceh government which cannot be far from the legitimacy of Islamic law. This situation creates that Aceh must do within the framework of Islamic Sharia principles. As global development, Aceh is faced with the demands of community life related to plurality. So it's interesting to explore how the development of plurality discourse. Plurality is an objective reality in the community of humankind, even it becomes the law of God or known as sunnatullah, so it can be understood that humans in life are different from each other even human paths also vary in religion. Circumstances like this, encourage researchers to find out how the views of Islamic dayah scholars in responding to the ideas and development of the plurality of Acehnese society. This becomes interesting because the cleric and dayah (zawiyah) are two inseparable things, because on one side of the dayah as an institution of community religious strengthening that is filled by the thoughts of the cleric when creating social events. The study was investigated using a combination of theories developed by various theories of religious phenomena and then the researchers made it as a foundation for the mind in discovering the views of Aceh's natural dayah when responding to the phenomenon of plurality. So this research uses the field research method with an interview approach to dayah scholars in Aceh. thus, this study found the result that plurality in the view of Acehnese scholars that plurality in the context of humanity is sunatullah, and plurality does not mean equating religion and believing in many gods.